Social networks usage implications at the level of medical services consumption in Romania - Gardan, Daniel Adrian; Andronie, Mihai; Gardan, Iuliana Petronela; Uta, Cristian (Journal of Economic Development, Environment and People, 2017)
The social networks usage degree increase is evident in recent years, this having implications for the consumption of the most types of products and services. A very special field of research is presented by the consumption of healthcare services, who, both in terms of consumption motivations, decisional buying process or consumer behavior is having peculiarities and specific traits. In this context, the present article aims to investigate the role that social networks use can have regarding changes within the consumer behavior in case of healthcare services consumption. In order to achieve the scientific endeavor, authors have conducted a quantitative marketing research as a field survey, using a questionnaire administered online to patients from different medical institutions, both from the public and private sector. The research results reveal key issues from the perspective of emotional involvement within consumption for the patients and the influence of key variables such as level of education, personality and lifestyle within social networks usage context.